Impact of systemic sclerosis-associated interstitial lung disease with and without pulmonary hypertension on survival: a large cohort study of the German network for systemic sclerosis - Moinzadeh, Pia; Bonella, Francesco; Oberste-Frielinghaus, Max; Weliwitage, Jithmi; Blank, Norbert; Riemekasten, Gabriela; Müller-Ladner, Ulf; Henes, Jörg Christoph; Siegert, Elise; Günther, Claudia; Kötter, Ina; Pfeiffer, Christiane; et al. (Chest, 2024)
Background: Pulmonary involvement is the leading cause of death in systemic sclerosis (SSc) and may manifest as interstitial lung disease (ILD), pulmonary arterial hypertension (PAH), or in combination of both (ILD with pulmonary hypertension [ILD-PH]). The aim of this analysis was to determine prevalence, clinical characteristics, and survival of these different forms within the registry of the German Network for Systemic Sclerosis. Research Question: Does SSc-associated ILD-PH or ILD without PH affect survival differently, and are there any risk factors that have an additional impact? Study Design and Methods: Clinical data of 5,831 patients with SSc were collected in the German Network for Systemic Sclerosis registry. Kaplan-Meier estimates were used to compare overall survival in patients with SSc-associated ILD-PH and ILD without PH with patients without pulmonary involvement and those with PAH. The Cox proportional hazard model was used to analyze the influence of pulmonary involvement and other potential predictors on patient survival. Results: Clinical data of 3,257 patients with a mean follow-up time of 3.45 ± 1.63 years have been included in our analysis. At baseline, ILD was present in 34.5%, whereas PH without ILD had a lower prevalence with 4.5%. At the end of follow-up, 47.6% of patients with SSc had ILD, 15.2% had ILD-PH, and 6.5% had PAH. ILD was more frequent in the diffuse cutaneous form (57.3%), whereas PAH did not differ significantly between SSc subtypes. Significant differences in baseline characteristics between PAH vs ILD-PH vs ILD without PH were found for age at diagnosis, sex, SSc subsets, antibody status, FVC, diffusing capacity of the lung for carbon monoxide, and therapy. Overall survival at 5 years was 96.4% for patients without pulmonary involvement and differed significantly between patients with ILD without PH, PAH, and being worst in patients with ILD-PH. Female sex (hazard ratio [HR], 0.3), higher BMI (HR, 0.9), and higher diffusing capacity of the lung for carbon monoxide values (HR, 0.98) were associated with a lower mortality risk. Interpretation: ILD is the most prevalent pulmonary involvement in SSc, whereas the combination of ILD and PH is associated with the most detrimental survival.
Online verfügbar: 13. August 2023, Artikelversion: 8. Januar 2024